Manfaat bermain tradisional dalam meningkatkan tumbuh kembang pada anak usia dini - dari, Eka Sari Wulan (Maliki Interdisciplinary Journal, 2024)
Play is an important aspect of child development, especially at an early age. the benefits of playing traditional games in supporting children's physical, cognitive, social-emotional, and language development. Traditional games offer a holistic approach that is not only fun but also educational, helping children to grow in a balanced and healthy way. traditional games are very important to improve growth and development in early childhood so that children know traditional games so that children know that traditional games are very good for children's physical and emotional development so that children can preserve Indonesian games and enjoy playing traditional games.